Electron-rich, Lewis acidic diborane meets N-heterocyclic aromatics: formation and electron transfer in cyclophane boranes - Widera, Anna; Filbeck, Erik; Wadepohl, Hubert; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2020)
Herein reported are the reactions of an electron-rich, Lewis acidic diborane with N-heterocyclic aromatics to give first members of an unprecedented family of highly charged cationic cyclophanes with diboranyl units. Tetracationic cyclophanes with 4,4‘-bipyridine/ 1,2-bis(4-pyridyl)ethylene and diboranyl units were synthesized and their redox chemistry was studied. Cyclisation of two diboranyl and two pyrazine units is accompanied by electron transfer from the diboranyl unit to the pyrazine. Our results pave the way for the integration of redox-active diboranyl units into cyclophanes and supramolecular structures.
Version of record online: February 27, 2020
Gesehen am 25.11.2021